2022
DOI: 10.1177/15589447211068184
|View full text |Cite
|
Sign up to set email alerts
|

The “Fight Bite” Saline Joint Loading Test: Effectiveness in Detecting Simulated Traumatic Metacarpophalangeal Arthrotomies

Abstract: Background: The saline load test is routinely used to recognize other joints’ traumatic arthrotomies; however, there are currently no studies evaluating the novelty of this test for metacarpophalangeal joints (MCPJs). This study aimed to investigate the effectiveness and sensitivity of saline load testing in identifying the traumatic arthrotomies of the MCPJs using human cadavers. Methods: This was a cadaveric study of 16 hands (79 MCPJs). Traumatic arthrotomies were created using 11-blade stab-incisions, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In arthroscopic test subjects, variability in joint volume thresholds of a particular joint can be dependent on capsular volumes and elasticity, synovial outpouching, underlying arthritic changes, plicae, and the patient's age 9,10,13,15,18 . Finally, arthrotomy wounds created for the various studies are not representative of what is seen in clinical practice, where periarticular wounds are of varying sizes 4,9,16,18,19 .…”
Section: Diagnostic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In arthroscopic test subjects, variability in joint volume thresholds of a particular joint can be dependent on capsular volumes and elasticity, synovial outpouching, underlying arthritic changes, plicae, and the patient's age 9,10,13,15,18 . Finally, arthrotomy wounds created for the various studies are not representative of what is seen in clinical practice, where periarticular wounds are of varying sizes 4,9,16,18,19 .…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Recently, an article was published evaluating "fight bite" injuries of the hand and the potential for TA. The article by Chughtai et al 16 indicated that the SLT with the addition of methylene blue at a volume of 0.32 mL is recommended to achieve a sensitivity of 99% when injected into the metacarpophalangeal joint, but the study is limited to cadaveric evaluation and further research is necessary for the clinical setting.…”
Section: Volume Thresholdsmentioning
confidence: 99%